Evaluation of the New York City Department of Probation's Drug Treatment Initiative, 1991-1994 - Falkin, Gregory P. ([Verlag nicht ermittelbar], 2000)
This study was undertaken to evaluate the New York City Department of Probation's initiative to place clients in specialized Substance Abuse Verification and Enforcement (SAVE) units for treatment and management. The main analytical strategy of this study was to determine whether clients who were appropriately matched to outpatient drug treatment were less likely to recidivate after treatment in this modality. The focus of the research was not so much on developing powerful prediction models, but rather on determining whether outpatient drug treatment was appropriate and effective for certain types of probationers. The evaluation research involved an in-depth analysis of a sample of 1,860 probationers who were sentenced between September 1991-September 1992 and referred to contracting outpatient drug treatment programs one or more times as of December 31, 1993. The following types of data were collected: (1) the New York City Department of Probation's demographic and drug use information, obtained during the presentence investigation and at intake to probation, (2) the Department of Probation's Central Placement Unit (CPU) database records for each referral made through the CPU, as well as monthly progress reports filled out by the treatment programs on each probationer admitted to drug treatment, (3) the New York State Department of Criminal Justice Statistics' data on criminal histories, and (4) probation officers' reports on whether clients were referred to treatment, the kind of treatment modality to which they were referred, and the dates of admission and discharge. Demographic and socioeconomic variables include age at first arrest and sentencing, gender, race or ethnicity, marital status, family composition, educational attainment, and employment status. Other variables include drug use history (e.g., age at which drugs were first used, if the client's family members used drugs, if the client was actively using heroin, cocaine, or alcohol at time of intake into treatment), criminal history (e.g., age at first arrest, number of arrests, types of crimes, prior convictions, and prior probation and jail sentences), and drug treatment history (e.g., number and types of prior times in drug treatment, months since last treatment program, number of admissions to a CPU program, and number of AIDS education programs attended).